Engineering the crystallinity of MoS2 monolayers for highly efficient solar hydrogen production. Issue 18 (21st April 2017) - Hai, Xiao; Zhou, Wei; Chang, Kun; Pang, Hong; Liu, Huimin; Shi, Li; Ichihara, Fumihiko; Ye, Jinhua
Abstract : This work reports the crystallinity engineering of MoS2 monolayers for efficient solar hydrogen production. Abstract : As a promising non-precious catalyst for the hydrogen evolution reaction (HER), molybdenum disulfide (MoS2 ), which is known to contain highly active edge sites and an inert basal plane, has attracted extensive interest. More recently, its amorphous counterpart has been found to have a higher HER activity, making it important to explore the effect of crystallinity on the HER performance of monolayer MoS2 . However, the posed technological challenges of preparing crystallinity tunable 2H–MoS2 monolayers hinder their further study. In this work, we report the successful synthesis of crystallinity-dependent MoS2 monolayers through liquid exfoliation of the corresponding crystallinity-controllable bulk precursors. Excellent cocatalytic performances of the proposed MoS2 monolayers for the photocatalytic HER were achieved and determined by their crystallinity. An apparent quantum efficiency as high as 71.6% can be achieved for the lowest crystalline monolayer MoS2 over cadmium sulfide under visible light irradiation at 420 nm. This work provides a facile way to synthesise crystallinity controllable MoS2 monolayers and elucidates that the HER activity can be further enhanced through crystallinity engineering, providing a new strategy to enhance the HER activity of monolayer MoS2 .